Development of Android-based New Student Admission Application at National University: Development of Android-based New Student Admission Application at National University - Muhamad Afriyan Kahfi; Septi Andryana; Aris Gunaryati (Jurnal Mantik, 2020)
Admission registration for new students will be entered or commonly known as PPMB is a route of years in every private and public university every year. Various information about the PPMB also published from: various media, among others: sources in various web campuses, as well as the following info about the registration, schedule and test location as well as information about graduation or absence. Many of the info also often forced students to always see the PPMB sites, if missed then: will always remain in the information about obtaining the latest information about PPMB. Therefore, the need to build an Android-based PPMB application into a proper alternative and with PHP programming language with PostgreSQL and Waterfall method is also a good choice. The research conducted in this phase is based on gradual, namely: the need for analysis, designing and design of the system, implement the system and also test the system. According to the test tests that have been conducted, it can be seen that: a PPMB application with the Android base could be used as an intermediary list for the new students. Other things from the analysis of the making of PPMB are also able to become intermediaries new information about the information registration with real-time so that the candidates from students have the convenience of getting the latest information on the PPMB site.